2016
DOI: 10.1155/2016/7592931
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Promotes Islet β-Cell Dysfunction in Rat Collagen-Induced Arthritis

Abstract: The aim of this study was to explore the possible mechanism of rheumatoid arthritis- (RA-) related abnormal glucose metabolism. The model of collagen-induced arthritis (CIA) was established by intradermal injection of type II collagen into Wistar rats; complete Freund's adjuvant injections were used as the control group. Fasting plasma glucose (FBG) was measured by the glucose oxidase method. Fasting insulin (FIns) and the expressions of IL-6 were detected by ELISA. Islet caspase-3 was examined by immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Consistently, there are increased levels of serum inflammatory markers, IL-6, in patients with type 2 diabetes, which can induce beta-cell apoptosis [ 19 , 31 33 ]. Our previous study also showed that the abnormal glucose metabolism was accompanied by the increased IL-6 expression [ 34 ]. Furthermore, in line with increased IL-6 expression, the apoptosis related enzyme Caspase-3 was also markedly increased in β cell.…”
Section: Inflammation and Abnormal Glucose Metabolismmentioning
confidence: 99%
“…Consistently, there are increased levels of serum inflammatory markers, IL-6, in patients with type 2 diabetes, which can induce beta-cell apoptosis [ 19 , 31 33 ]. Our previous study also showed that the abnormal glucose metabolism was accompanied by the increased IL-6 expression [ 34 ]. Furthermore, in line with increased IL-6 expression, the apoptosis related enzyme Caspase-3 was also markedly increased in β cell.…”
Section: Inflammation and Abnormal Glucose Metabolismmentioning
confidence: 99%
“…Interestingly, IL-6 levels were reduced in both CP and LPP groups by PPD90, concomitant with the return of glucose tolerance to control values. Some studies have found that high concentrations of IL-6 could promote β-cell apoptosis and contribute to glucose intolerance (Jin et al 2016). However, since β-cell area did not change at any time point after parturition in LPP mice, it is more likely that IL-6 is exerting effects on non-islet tissues.…”
Section: Journal Of Endocrinologymentioning
confidence: 89%
“…The literature proves that potential targets can interact with each other. To explore the possible mechanism of the rheumatoid arthritis- (RA-) related abnormal glucose metabolism, researchers showed that the apoptosis-related enzyme Caspase-3 was significantly increased with upregulation of IL-6 expression [ 31 ]. MMP9 released after nerve injury is involved in the activation of microglia, leading to the release of IL-6 by microglia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%